RETIREMENT READINESS UNVEILED: EXPLORING THE LIVED EXPERIENCES AND CHALLENGES OF FINANCIAL CONFIDENCE AMONG COLLEGE INSTRUCTORS IN CEBU’S STATE UNIVERSITY - Debalucos, Ivy Claire; Polinar, Mark Anthony N. (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The education sector is a linchpin of national development, and the financial well-being of educators is a vital component. As college instructors approach the end of their careers, feeling financially secure becomes a critical part of their long-term planning. Their stories and experiences are of profound importance; they have dedicated their lives to teaching and shaping future generations. Understanding what helps or hinders their financial confidence can help create better support systems, ensuring they enjoy a comfortable and secure retirement. College instructors, who dedicate their careers to shaping the minds of future generations, often face unique financial challenges. This study aims to explore the factors contributing to the financial retirement confidence of college instructors at a state university in Cebu, Philippines. Using a qualitative phenomenology approach, interviews were conducted with college instructors aged 57 to 65. The findings revealed that higher pension amounts and fewer dependents significantly boost retirement confidence, while financial obligations pose barriers. Themes like financial management, investments, professional development, and health investment were identified as crucial components for retirement security. The study concludes that comprehensive financial planning, including increased pension benefits and financial literacy programs, can enhance retirement confidence. It recommends that institutions support instructors through resources and programs for effective retirement planning. These findings contribute to understanding the multifaceted nature of retirement confidence and provide a foundation for further research across different educational settings.